Development of an Early Surgery Nursing Service System for the Older Patients with Hip Fracture in Singburi Hospital - Meehanpong, Pranee; Boonsin , Suneerat; Baiteang, Chutima (Nursing Journal of The Ministry of Public Health, 2023)
This research and development study aimed to develop and evaluate the outcomes of an early surgical nursing service system for the older patients with hip fracture in Singburi Hospital. The research consisted of the following 4 steps: 1) Exploring current conditions and problems, 2) Designing a nursing service system, 3) Implementing the nursing service system, and 4) evaluating the results. The purposively sampled group consisted of 46 professional nurses and 38 elderly patients with hip fracture who received early surgery nursing services. The research instruments included professional nurses’ satisfaction, the emergency surgical care system compliance assessment form, patients’ self-care practice knowledge, the Barthel Index (BI), and service quality outcomes. The data were analyzed using descriptive statistics. The findings revealed that the early nursing service system was effective, in that 1) the satisfaction of registered nurses was high (Mean=4.27, SD=.40), 2) the practice of early surgery nursing services system was at a high level (100%), 3) the patients’ self-care practice knowledge was at a high level with scores of 15-20 (92.10%), the Barthel Index (BI) at 6 weeks after surgery was high (100%), and the outcomes of service quality found that the waiting time for surgery, the rate of postoperative complications, the length of stay (LOS) and costs had decreased, while the percentage of patients receiving surgery within 72 hours had increased.